The Relationship Between Health Care Performance and Mothers' Satisfaction with Toddler Services Integrated Health Post in RW 01 East Pademangan - Ria Efkelin; Khalida Ziah Sibualamu; Astrid Komala Dewi (Lembaga Pengembangan Kinerja Dosen, 2025)
Study This aim For to determine the Relationship between Health Cadre Performance and Toddler Mother Satisfaction in Posyandu Services in RW 01 East Pademangan, North Jakarta. This type of research is quantitative with a Cross-Sectional design . The data collection technique for this study uses primary data and secondary data. Primary data were obtained directly through filling out questionnaires by mothers of toddlers at Posyandu RW 01 East Pademangan, while secondary data were obtained from sources that could support the research, including documentation and literature . The data analysis of this study used bivariate analysis which was carried out to determine the influence between variables x and y in the form of a static Likelihood Ratio Chi-Square (G - Test ) test . The results of the study showed that the performance of health cadres at Posyandu RW 01 East Pademangan was generally in the good category. This shows that cadres have carried out their roles optimally in providing health services to mothers and toddlers. Most toddler mothers are satisfied with the services provided by Posyandu cadres. This illustrates that the services provided are sufficient to meet the expectations and needs of mothers of toddlers in the area, and there is a significant relationship between the performance of health cadres and the satisfaction of mothers of toddlers at Posyandu RW 01 East Pademangan. This finding indicates that the better the performance of the cadres, the higher the level of satisfaction of mothers of toddlers with Posyandu services